Lymph node ratio-dependent prognosis stratification and postoperative radiotherapy utilization in T1-2N1 oral cavity carcinoma. (July 2022) - Wang, Jingbo; Liu, Yang; Shayan, Gulidanna; Ma, Yuchao; Yi, Junlin
Highlights: T1-2N1 OCSCC is a setting with worse-than-expected outcome. Peak hazard period of progression occurs within the 2nd year after treatment. LNR is an important prognostic determinant for pT1-2N1 OCSCC. LNR > 5.5% indicates that pT1-2N1 OCSCC may gain survival benefit from PORT. Abstract: Objective: Pathological T1-2N1 oral cavity squamous cell carcinoma (pT1-2N1 OCSCC) is a setting with intermediate prognosis whilst without consensus regarding the utilization of postoperative radiotherapy (PORT). This study aimed to investigate the prognostic value of lymph node ratio (LNR) and to further examine its clinical validity for guiding PORT in pT1-2N1 OCSCC. Methods: OCSCC patients who received surgery between 2010 and 2015 with at least 6 lymph nodes dissection were extracted from the Surveillance, Epidemiology and End Results (SEER) database. Time-dependent receiver operating characteristic (ROC) analysis was used to identify the optimal cutoff of LNR. Multivariable Cox regression analysis was employed to assess the prognostic value of LNR. Impact of PORT was evaluated in respective subgroups stratified by LNR. Results: A total of 870 OCSCC patients with pT1-2N1 diseases were eligible for analysis. The 5-year overall survival (OS) and disease-specific survival (DSS) was 57.2% and 67.9% respectively. Time-dependent ROC analyses for OS and DSS concordantly revealed 5.5% as the optimal cutoff of LNR. Significantly higher risks of death (HR = 1.610, 95% CI: 1.139–2.276) and disease-specific death (HR = 1.731, 95% CI: 1.101–2.723) were unveiled in patients with LNR > 5.5%. PORT related improvement on OS (5-year rate: 57.6% vs. 47.3%, p = 0.095) and DSS (5-year rate: 71.0% vs. 53.8%, p = 0.030) was only found in LNR > 5.5% subgroup. Conclusions: LNR > 5.5% is indicative of inferior outcome in pT1-2N1 OCSCC, warranting the utilization of PORT in this sub-setting.